Loss of heterozygosity in the short arm of human chromosome 3 in sporadic lung cancer (2010)
ABSTRACT: Introduction: Loss of Heterozygocity (LOH) in the short arm of human chromosome 3 (3p) is a frequent event in different types of sporadic tumors, including lung cancer (LC). Aim: To determine 3p LOH in LC samples using 17 microsatellite markers. Methodology: In a pilot study on volunteers, thirteen LC biopsies (tumor tissue) and 4 ml of blood (normal tissue) from the same patient were collected. DNA extraction and Polymerase Chain Reaction (PCR) were performed with 17microsatellite markers to analyze LOH. Amplified fragments were run on 6% denaturalizing polyacrilamide gels and were visualized by using silver stain. Descriptive analysis was performed for each region on the 3p chromosome. Results: All tumors were informative for one or more of the analyzed markers. LOH was found in one or more loci in eleven samples (84.6%). The markers with major LOH were UBE1L (23.1%), D3S1317, D3S1300, D3S1284, D3S1274, D3S3049,and D3S1577 (15.4%). Three samples showed microsatellite instability (changes in the length of the microsatellite) indifferent loci. The percentages of LOH for the regions of 3p were: 17.6 % for 3p24-25, 11.62% for 3p21-22, 20% for 3p13-14, and 18.42% for the 3p12 region. Conclusions: Chromosomal regions with allelic loss were identified where probably other GSTs involved in the development of the LC are localized. It should increases sample size and marker number in order to narrow a minimal region and to identify a unknown gene involved in LC.